The Influence of Company Age, Company Size, Liquidity, Premium Income, And Investment Returns On The Profit Of Islamic Life Insurance Companies In Indonesia For The Period 2019-2024 - Sofiyatun Nisa; Mukhsin, Moh.; Suhartini, Nani (JIES : Journal of Islamic Economics Studies, 2025)
The purpose of this study was to determine the effect of Company Age, Company Size, Liquidity, Premium Income and Investment Returns on Profit of Sharia Life Insurance Companies in Indonesia. The sampling technique used purposive sampling technique for 6 companies for the period 2019-2024. Secondary data sources are based on the annual financial reports on the official websites of each company. The analysis technique used in this study uses Eviews 12 software through panel data regression analysis. The results of this study indicate that partially the age of the company has a negative and significant effect on profit. Liquidity, premium income, and investment returns have a positive and significant effect on profit. While company size has no effect on profit. Meanwhile, simultaneously the age of the company, the size of the company, liquidity, premium income and investment returns on the profit of Islamic life insurance companies in Indonesia.